Problem-solving training: effects on nursing students’ adherence, confidence, and application of problem solving to deal with the barriers to adherence to routine infection control practices - Hamed, Abubaker M.; Moralejo, Donna; Pike, April; Curran, Vernon (International Journal of Infection Control, 2023)
Background: Adherence to routine practices (RP) in infection control can be influenced by a number of barriers, which can potentially be dealt with using problem solving (PS) as a new approach. Aim: This study examined the effects of a problem-solving educational program (PSEDP) on nursing students’ adherence, confidence, and application of PS to address the three identified common barriers to RP adherence. Method: A controlled before and after study was conducted at two nursing schools in Eastern Canada. A total of 94 nursing students participated, with 62 students in the intervention group and 32 in the control group. Students in the intervention group received the PSEDP, while the control group received no intervention. Data from both groups were collected using a problem-solving questionnaire. Results: Overall, no significant differences were found between the intervention and control groups in their adherence to RP (P = 0.580), confidence in using PS (P = 0.602), and application of PS (baseline P = 0.161, post-program P = 0.618) to deal with the three identified barriers to RP adherence. However, we found significant differences in the subscale analysis of student confidence to deal with the barrier of high nursing workload (P = 0.032) and student adherence to some of the RP components (P < 0.05). Conclusion: The educational program provided an opportunity for the students to learn about PS to address the three identified barriers. Some improvements were found but they were smaller than expected, possibly due to limited time for practice in the clinical setting following the intervention.